Are Artificial Intelligence (AI) Skills a Reward or a Gamble? Deconstructing the AI Wage Premium in Europe - Konstantinos Pouliakas; Giulia Santangelo (Institute of Labor Economics (IZA), 2025)
Understanding the labour market impact of new, autonomous digital technologies, particularly generative or other forms of artificial intelligence (AI), is currently at the top of the research and policy agenda. Many initial studies, though not all, have shown that there is a wage premium to AI skills in labour markets. Such evidence tends to draw on data from web-based sources and typically deploys a keyword approach for identifying AI skills. This paper utilises representative adult workforce data from 29 European countries, the second European skills and jobs survey, to examine wage differentials of the AI developer workforce. The latter is uniquely identified as part of the workforce that writes programs using AI algorithms. The analysis shows that, on average, AI developers enjoy a significant wage premium relative to a comparably educated or skilled workforce, such as programmers who do not yet write code using AI at work. Wage decomposition analysis further illustrates that there is a large unexplained component of such wage differential. Part of AI programmers' larger wage variability can be attributed to a greater performance-based component in their wage schedules and higher job-skill requirements.
Keywords: J24; J31; J71; M52; 330; wage differentials; skills; artificial intelligence; performance-based pay